Comportamentos de crianças com transtorno do espectro autista com pares nos contextos de educação musical e recreio escolar - NASCIMENTO, Paulyane Silva do (Universidade Federal do Pará, 2019)
The present study investigated personal characteristics, environmental and behavioral factors that may enable or impede/prevent the social interaction of children with ASD with their peers. Were analyzed the benefits of music education context as a promoter of this interaction. To organize the issuance of these forms of behavior, were elaborated the "Protocol observation of behaviors of children with Autism Spectrum Disorder (ASD) with their peers". The study investigated two children, male, diagnosed with ASD, of the Garden I, of the regular schools of the city of Belém/PA. The children were six and five years old, respectively, and were matriculated in percussion’ classes in Music’s School from Belem/PA. Three sessions were analyzed at regular school environment (during recreation), lasting 20 min each; and 8 sessions in the context of music education (lessons percussion), 30 minutes each. The results showed that the behaviors among children with ASD and their peers occurred in both contexts occurred in both contexts, however reaching higher frequency in the context free (regular school / recreation). As to the benefits of music education, The participant 1 (6 years), whose profile was marked by the acceptance of physical contact, and a search for persons, obtained the increase of functional initiative's behaviors and decreased of non-functional's responses. Observed it was also the occurrence of functional initiatives through repetitive behaviors, indicating that this peculiarity could do helping the child to approach and interact with peers. Already the participating 2 (5 years), with a profile marked by touch, emotional expression appropriate to the context, and social reciprocity (though occasionally), we observed a strong influence of the adult in the child's behavior. This influence was positive (to reduce the emission of non-functional behaviors) and negative (when had the high assist disregarding the child's strengths and hindering its interaction with peers). We conclude that given the low frequency of such behaviors, we cannot say that the changes are related exclusively to this environment, but only to the contiguity of the possibilities represented by the profile of the child and openness of each context for the expression and stimulation of these capabilities, as well as for the provision of tools to permit the seizure or reinforce behaviors conducive to social interaction.